Study on docking guidance algorithm for hybrid underwater glider in currents. (1st October 2016) - Yang, Canjun; Peng, Shilin; Fan, Shuangshuang; Zhang, Shaoyong; Wang, Pinfu; Chen, Ying
Abstract: The development of a novel type of hybrid underwater glider (HUG) that combines the advantages of buoyancy-driven underwater glider and propeller-driven autonomous underwater vehicle (AUV) has recently received considerable interest. HUG is designed with a rotatable thruster to ensure the enough maneuverability of the vehicle for underwater docking. Unlike the fixed funnel-type dock, the dock proposed here can rotate actively to allow the vehicle to approach the docking station from most range of directions providing better accessibility for the vehicle. Considering that the ocean current may have a significant impact on the HUG, a pursuit guidance algorithm with current compensation is presented. The performance of the guidance algorithm is compared with other existing guidance algorithms, such as pure pursuit guidance and proportional navigation guidance by simulation based on the dynamic model of HUG. Moreover, underwater docking experiments are conducted to validate the feasibility of the docking system and the effectiveness of the proposed guidance algorithm. The experimental results indicate that the proposed algorithm compensates well for the current disturbances on HUG docking mission and the HUG can dock with the rotatable dock entrance successfully. Highlights: A docking scheme consists of a hybrid underwater glider with a rotatable thruster for high maneuverability and a rotatable dock station providing better accessibility. The docking control problem for underwater vehicle is described mathematically. A pursuit guidance algorithm with current compensation is presented, which takes both the view range of the sensors and the ocean current disturbances into account.